Improve energy storage performance by tweaking grain size and widening the energy bandgap in modified BaTiO3 ceramics - Alkathy, Mahmoud. S.; Milton, Flavio Paulo; Zabotto, Fabio L.; Gatasheh, Mansour K.; Kassim, H. A.; Raju, K. C. James; Eiras, Jose A. (Indian journal of physics, 2025)
The Ba0.92(La0.50Li0.50)0.08TiO3 (BLLT0.08) ceramics have been synthesized using both microwave sintering (MWS) and conventional sintering. Our study focused on the synthesized ceramics’ crystal structure, morphology, dielectric, ferroelectric, and energy storage properties. The results indicate that both samples have a tetragonal phase structure. Furthermore, the MWS method improves grain refinement and promotes a more consistent grain size distribution. The MWS approach reduces remnant polarization from 3.36 to 2 kV/cm while increasing breakdown strength from 79 to 104 kV/cm. Bandgap energy widening and small grain size are responsible for the high breakdown strength. The MWS-sintered BLLT0.08 compound has a high energy storage density (Wrec) of 0.81 J/cm3 and an efficiency (η) of 91%. The findings of this study suggest that decreasing grain size while increasing band gap width may provide insight and assist researchers in proposing a novel strategy to improve the energy storage performance of ferroelectric materials. This study contributes to the ongoing investigation of improved ways to enhance ceramics’ functional properties, which has implications for various energy storage device applications.The microwave sintering technique improves the energy storage performance of materials, making it ideal for energy storage applications. Microwave sintering often requires less processing time than conventional sintering, making it useful for large-scale manufacturing and potentially resulting in cost savings. The short processing duration promotes fine grain size. Maintaining the broad bandgap energy of BLLT0.08 ceramics is critical, resulting in enhanced breakdown strength and better energy storage performance.